A Comparative study of Morphological and Agronomic Characters of a Few Introduced Soil Conservation Grasses in the Plains of Madras State - Pillai, K.M.; Ramachandran, K. (Journal of Soil and Water Conservation, 2022)
Research on Soil Conservation depends much on the efficiency of the grass cover on the contour bunds and terraces. Not all grasses introduced are found suitable in the tropical climate of the plains of Madras State. A few introduced grasses, based on their drought resistance and vigour were found promising in the plains. Of these Cenchrus eiliaris, C. glaucus, Digitaria sp., and Panicum  antidotale are worth mentioning (Madava Rao and Ramaswamy 1965). The first two grasses were found to be ideal for soil conservation practices in the plains (Madhava Rao et al., 1964). Being a hardy perennial with stout rhizomes, C. glaucus not only stands drou-ghty conditions but also regenerates very quickly after the rains. It has profuse fibrous roots which make it a valuable soil binding grass (Daniel Sundararaj et al 1966). Recently few more grasses viz. Eragrostic superba Prnicun maximum ( var colonian) peanisetum merkeril Erianthus were also found equally good for soil conservation puposes.